Fault-tolerant Gossip Graphs Based on Wheel Graphs - Vilyam H. Hovnanyan; Suren S. Poghosyan; Vahagn S. Poghosyan (Изд-во НАН РА)
The gossip problem (telephone problem) is an information dissemination problem where each of n nodes of a communication network has a unique piece of information that must be transmitted to all the other nodes using two-way communications (telephone calls) between the pairs of nodes.
Keywords: Mathematics; Computer software; Graph theory